The effects of a nursing care plan incorporated with a decision support system on ventilator associated pneumonia: A case study - Bolat, Özgür; Gülenç, Nalan; Özkan, Elife; Aydın, Nuran; Köse, İlker (SciTePress, 2020)
The risk of pneumonia is high in patients who are ventilated in intensive care units (ICUs). Without proper and adequate care, this risk and the mortality rate increases. In a study conducted by the infection committee of our hospital (tzmir Tire State Hospital, the first digital (Stage 7) hospital in Turkey in 2016), it was found that the rate of ventilator-associated pneumonia (VAP) cases increased had increased over three years (2015-17) and was well above the national average. In this study, VAP prevalence in our ICU and the associated extra medication costs were calculated. Furthermore, nursing care plans related to VAP were reviewed and improvements were made according to international standards. The care plan was triggered by criteria defined in a clinical decision support system (CDSS) on the hospital information management system (HIS), and monitorization was conducted to ensure that nurses implement the care plan in a comprehensive and timely manner. As a result of the change, the rate of VAP cases. which had risen to 4.5% in 2017, was reduced to 0.5% in 2018. Similarly, we achieved cost reductions of 90.87% for VAP-based extra medications. Based on these results, it can be suggested that CDSS-supported nursing care can significantly reduce the risk of VAP and increase patient safety in the ICU.
Keywords: Ventilator Associated Pneumonia; Nursing Care; Decision Support System; Intensive Care Unit